2004
DOI: 10.1002/adv.20014
|View full text |Cite
|
Sign up to set email alerts
|

Reactive extrusion of poly(urethane‐isocyanurate)

Abstract: ABSTRACT:Reactive extrusion of poly(urethane-isocyanurate) (PUIR) was studied in an intermeshing corotating twin-screw extruder. Toluene diisocyanate (TDI) and polypropylene glycol (PPG) were used as initial materials with dibutyltin dilaurate (DBTDL) as catalyst. The reaction was first examined in a batch reactor as well as in an internal mixer in order to obtain the kinetics and temperature/torque evolution trends during the formation of PUIR, respectively. For the specified screw speed and temperature profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…8). This result was also observed by Lomölder et al [23] on IPDI, and similar results were obtained on tolylene diisocyanate (TDI) for which orthoand para-NCO groups reactivities get closer in the presence of catalyst [39].…”
Section: Influence Of Catalyst Concentrationsupporting
confidence: 90%
See 1 more Smart Citation
“…8). This result was also observed by Lomölder et al [23] on IPDI, and similar results were obtained on tolylene diisocyanate (TDI) for which orthoand para-NCO groups reactivities get closer in the presence of catalyst [39].…”
Section: Influence Of Catalyst Concentrationsupporting
confidence: 90%
“…temperature enhancement of the primary NCO reactivity rather than the secondary one, was related by others when reacting IPDI with different alcohols in the temperature range 20-100 8C [23]. Similarly, the significant influence of temperature on selectivity was quoted for TDI molecule [39]. It was reported that at 25 8C the NCO group in the para position is 8 to 10 times as reactive as that in the ortho position, but at 100 8C both NCO have similar reactivities.…”
Section: Influence Of Temperaturementioning
confidence: 85%
“…[7][8][9] It was reported that it was feasible to fabricate PU via reactive extrusion, but a further chain extension was followed. [10][11][12] PCL can also be obtained by a one-step reactive extrusion. 13 Thus, it is possible to simultaneously perform the ring-opening polymerization of ecaprolactone (CL) and the urethane reaction to form PCLU via one step in an in situ reactive extrusion with the proper initiator.…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact reaction mechanism of polyurethane formation is more complex, the kinetics of reaction of diisocyanate with dihydroxyl compound is often expressed successfully by a second-order rate equation [1,2,7,24,25]:…”
Section: Reaction Kineticsmentioning
confidence: 99%
“…The kinetics of formation of polyurethanes has been studied by several authors [7][8][9][10]. The most common methods for data acquisition are titration, Fourier transform infrared (FTIR), adiabatic temperature rise (ATR), and gel permeation chromatography (GPC).…”
Section: Introductionmentioning
confidence: 99%